Indic-Vernacular Bitexts from Thailand: Bilingual Modes of Philology, Exegetics, Homiletics, and Poetry, 1450–1850. - WALKER, TRENT (Journal of the American Oriental Society)
In the late first and early second millennia, mainland Southeast Asians created sophisticated techniques to accurately and efficiently render Pali into local vernaculars, including Burmese, Khmer, Khün, Lanna, Lao, Lü, Mon, and Siamese. These techniques for vernacular reading, parallel to approaches for reading Latin in medieval Europe and Literary Sinitic in Japan, Korea, and Vietnam, led to the development of bitexts that contained a mix of Pali and vernacular material. Such bitexts, arranged in both interlinear and interphrasal formats, gradually allowed second-millennium Southeast Asian writers to sprout a vernacular literature from the established branches of Pali genres. Bitexts themselves formed the basis for a new literary style that stemmed from the techniques of vernacular reading, a style that set the standard for belles-lettres until the early twentieth century. The spread of Pali-vernacular bitexts in Southeast Asia allowed for the literary elevation of the vernacular without renouncing the cosmopolitan idiom of Pali. To support these arguments, this article draws on some of the earliest examples of bitexts in Central Thailand (Siam) and Northern Thailand (Lanna). These include a hitherto undeciphered form of manuscript annotation in seventeenth- to nineteenth-century Siam; two of the oldest palm-leaf documents surviving in any Tai language, from sixteenth-century Lanna; and the oldest known Pali-Siamese literary work, thought to be composed in 1482. These bitexts provide detailed evidence for vernacular reading and the emergence of vernacular literature in mainland Southeast Asian in general and Thailand in particular.